2004
DOI: 10.1016/j.wear.2003.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The friction, mobility and transfer of tribological films: potassium chloride and ferrous chloride on iron

Abstract: The tribological properties of FeCl 2 , measured using an ultrahigh vacuum tribometer, are compared with those of KCl. The friction coefficient of an FeCl 2 film evaporated onto iron in ultrahigh vacuum decreases to ∼0.08 after the deposition of a film ∼40 Å thick. This value is in good agreement with that measured for reactively formed FeCl 2 films in a pin and v-block apparatus. The contact resistance also increases at the same FeCl 2 thickness as that at which the friction coefficient reaches its minimum va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
(63 reference statements)
2
11
0
Order By: Relevance
“…It has also been shown that a ferrous chloride film evaporated onto iron in ultrahigh vacuum reduces the friction coefficient to $0.08, in good agreement with the values found above for model lubricants comprising small chlorinated hydrocarbons dissolved in a poly a-olefin [10]. Transfer of the FeCl 2 from the iron to the tungsten carbide tribopin was also observed.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…It has also been shown that a ferrous chloride film evaporated onto iron in ultrahigh vacuum reduces the friction coefficient to $0.08, in good agreement with the values found above for model lubricants comprising small chlorinated hydrocarbons dissolved in a poly a-olefin [10]. Transfer of the FeCl 2 from the iron to the tungsten carbide tribopin was also observed.…”
Section: Introductionsupporting
confidence: 84%
“…Shown as an inset to (a) is the variation in friction coefficient with films thickness for FeCl 2 evaporated onto iron.the completion of the first. A similar situation applies in the case of evaporated FeCl 2 layers and a similar analysis in this case reveals that the first-layer FeCl 2 film thickness is 10±2 Å[10]. Ferrous chloride forms a layer structure with the thickness of each layer being about $8.5 Å[18], in good agreement with the estimate of the first-layer thickness of the evaporated film.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The chamber was equipped with an ultrahigh vacuum-compatible tribometer, which simultaneously measures normal forces, lateral forces, and the contact resistance between the tip and substrate [1][2][3][4][5]. All tribological measurements were made using a single pass in the same direction with a sliding speed of 4 9 10 -3 m/s on a freshly prepared surface, and the tribopin was heated by electron bombardment in vacuo prior to each experiment to clean it.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated previously that a complete monolayer of an inorganic halide deposited onto an iron substrate substantially lowers the friction coefficient from *2 for the clean iron surface to less than 0.3 when the surface is covered by such a layer of KCl [1][2][3][4]. These measurements were carried out for a tungsten carbide pin sliding over a freshly deposited film on a clean metal substrate in an ultrahigh vacuum, where it has been shown that the polished and annealed metal substrate is much smoother than the tungsten carbide ball [5].…”
Section: Introductionmentioning
confidence: 99%